(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to study the potential and develop skills in textile handicrafts of Thai Lanna ethnic group in Sukhothai Province. The research process was carried out as follows: 1) study the community context, 2) community-based knowledge transfer, and 3) the development of textile products using quantitative and qualitative research methods. Research tools include interviews and questionnaires, collected data from group conversations, and the satisfaction was assessed by a specific sampling group from key informants from Thai Chanasuek Sub-District Community, Thung Saliam District, Sukhothai province, in the group of 30 people by analyzing descriptive statistics. Research results showed that 1) the Thai Lanna ethnic community is a community that immigrated from Lampang Province with the traditions, culture, language, traditions and weaving with a flower pattern which has been the identity of the community and has been produced as costumes, blankets and bags. 2) The knowledge of the weaving production of the community arises from the dynamic exchange of knowledge between the conveyer and the recipient of knowledge in the form of explicit knowledge. Knowledge consolidation and the conversion of knowledge were applied to enhance the textile products and the economic base of Thai Chanasuek Sub-District Community. 3) Woven fabric pattern design, using the concept of Neem flower to develop the pattern by using cotton brocade technique and processing of woven fabrics into clothing with satisfaction in utility, shape and beauty. The average was at a very good level